New littoral, shelf, and bathyal Paratanaidae (Crustacea: Peracarida: Tanaidacea) from New Zealand, with descriptions of three new genera - Bird, Graham J.; Bamber, Roger N. (Zootaxa, 2013)
Three new genera, Acallocheirus, Aparatanais, and Penteparatanais, and seven new species of the paratanaid subfamily Paratanaidinae are described from New Zealand. New records of three previously known species Atemtanais taikaha, Paratanais paraoa, and P. tara, are also given. Paratanais denticulatus, P. intermedius, P. malignus, P. spinanotandus,and P. vicentetis are transferred to Aparatanais. A key is given to all paratanaidin genera and the NZ Paratanais species. In NZ waters, paratanaids are now known from the littoral zone to 908 m in the bathyal regions of the Chatham Rise and Hikurangi Margin, several of the offshore species being recorded in bryozoan mats. All but one appear to be endemic but may have sibling species elsewhere, particularly in the Southern Hemisphere. Supplementary notes are given on two Australian species P. maleficus and P. perturbatius that clarify their description and diagnostic characters.